Pork free restaurants attributes, muslim customers trust and satisfaction, re-patronization and dissemination of information / Mohamad Izham Mohamad Haroun - Mohamad Haroun, Mohamad Izham (2015)
Halal is not only term of religion but it governs cleanliness and purity and everything from the food that we consume to the business transactions that are performed in our daily lives. As products and services are closely associated with restaurant businesses therefore producing Halal foods, beverages, services and environment play an important role that influence feelings, decision making, behavior and expectation towards patronizing the restaurant among the Muslim customers. Seeing that Malay Muslim customers are the highest markets in Malaysia, the demand in ascertaining the products consumed are religiously fit or halal in the restaurants is obviously apparent and this is as indirect signal to primary target of Malaysian Muslim customers'. Nevertheless, owing to multi religious and multi ethnics of Malaysia, not all local restaurants are systematically Halal and with that a new ‘Islamic’ image known as Pork Free restaurants are rapidly emerging especially in the large cities. Pork Free status is in fact becoming a new marketing strategy in capturing the Muslim market. This scenario demands the understanding of how and to what extent that the pork free restaurant attributes influence Muslim customer attitudes, trust and satisfaction and subsequent their purchase behavior. This study is empirically examining the pork free restaurants attributes on Muslim customers’ attitudes, trust and satisfaction and their re- patronization and dissemination of information. To integrate and entwined the findings both quantitative (customers point of view) and qualitative (restaurant operators) approaches were opted. Through a self-administered survey among the Pork free restaurants Muslim customers, 319 questionnaires were collected and 20 pork free restaurant operators were successfully interviewed. With the application of various statistical analyses ranging from descriptive and inferential statistics used to answer the objectives, research questions and hypotheses and pen portrait interpretation of the qualitative information, some useful insights pertaining to the issues investigated was significantly obtained. Of two types of Pork free restaurant investigated, the one that serving food without alcohol or PFNA has received more confident and closer among the Muslim customers heart either in terms of food offering, service render and ambience provided compared to the one that serving alcohol or PFWA. Their confident level is further strengthened with their positive trust and satisfaction therefore will always and more often to patronizing PFNA restaurants and no hesitation of sharing their good experience with other fellow Muslim families and friends and encourage them to patronize PFNA restaurants as opposed to slightly agree with PFWA. Despite this, information gathered from the interviewed provide evidences that some of the pork free restaurant either without alcohol (PNFA) or with alcohol served (PFWA) are not fully halal as no valid halal certification received and did not fully conform to the halal standards. The operators are only used Pork Free as their Halal symbol or camouflage to attract Muslims customers although in actual fact and not to exaggerate that some of the ingredients used are doubtful in term of it halalness. These scenario directly create varying consequences and implications for the Muslim customers itself, pork free restaurant operators as well the relevant authorities.